CHINA: A CASE OF ‘MERCANTILISM’ IN A BACKWARD COUNTRY? - Silvio Beretta; Giuseppe Iannini (European Scientific Journal, ESJ, 2014)
Despite being criticized for its inconsistencies, China’s mercantilism is considered a commonplace in the literature focused on Chinese economic development. This paper intends to criticize the foundations of China’s ‘monetary’ and ‘financial’ mercantilism arguing that both provide only a feeble explanation of its economic success. In particular, rather than echoing the practices of classical mercantilism, such supposed ‘mercantilist’ approach, on the contrary. Reflects the Gerschenkronian model of development, according to which the growth of the ‘backward’ countries is based massively on banks and State support.